Educational software for stress analysis of non-idealized closed thin-walled sections - Syed Mohamed Ali, Jaffar; Ali, Mir Owais; Riyadh, Miah Mohammed (2018)
Aerospace structures such as fuselage and wings are made of typical thin-walled closed sections and the detailed stress analysis of such closed thin-walled structures can be tedious and time consuming due to its statically indeterminate nature of the problem. In the present work, an educational software for the stress analysis of such non-idealized thin-walled closed sections has been developed that complements tradi-tional methods of teaching and learning. The software developed is able to generate any given closed cross section which are subjected to bending, shear, and torsional loads and compute the resulting stresses on the cross section. Results from literature have been used to validate the results from the software. The software has been developed using Graphical User Interface (GUI) in MATLAB which makes the soft-ware very user friendly. The software is expected to be an effective teaching and learning tool of courses on thin-walled structures and air-craft/automotive structures.